Carbide Derived Carbon Supported Pt Nanoparticles with Optimum Size and Amount for Efficient Oxygen Reduction Reaction Kinetics. Issue 4 (8th March 2017) - Jäger, R.; Härk, E.; Kasatkin, P. E.; Pikma, P.; Joost, U.; Paiste, P.; Aruväli, J.; Kallio, T.; Jiang, H.; Lust, E.
Abstract : The oxygen reduction reaction (ORR) kinetics was studied on catalysts with a very low Pt loading (3.5, 8.3 and 12.4 wt%) and small Pt nanoparticles (from 2.0 to 3.9 nm) deposited onto the molybdenum carbide derived carbon. Three different platinum catalysts were synthesized and characterized by the high resolution transmission electronmicroscopy, in situ atomic force microscopy, inductively coupled plasma mass spectrometry, X-ray diffraction and nitrogen sorption analysis. The electrocatalytic activity toward ORR was analyzed with rotating disk electrode and cyclic voltammetry methods in 0.1 M KOH, 0.05 M H2 SO4 and 0.1 M HClO4 aqueous solutions. The Pt mass corrected current ( j Pt ) values depend on the Pt loading and at fixed Pt weight percent in the catalyst j Pt increases in the sequence: 0.1 M KOH < 0.05 M H2 SO4 < 0.1 M HClO4 . The catalyst containing 8.3 wt% platinum with the mean particle size of 3.3 nm is found to be optimum for ORR in various electrolyte solutions. The physical and electrochemical methods have been used for estimation of the electrochemically active surface area of the Pt catalysts.